Modelling in vitro gastrointestinal digestion of egg white gel matrix by laser-backscattering imaging. (March 2022) - Verdú, Samuel; Gallego, Marta; Barat, José Manuel; Talens, Pau; Grau, Raúl
Abstract: The objective of this work was to test the capability of laser-backscattering imaging technique to model changes produced throughout in vitro gastrointestinal digestion of chicken egg white gel as protein matrix model. Evolution of the matrix sample was monitored by analysing protein digestibility, zeta potential, particle size, and imaging every 20 min during the digestion process. Laser-backscattering was based on capturing the diffraction patterns generated by laser-light after being transmitted through matrix samples. Differences in imaging data were observed for the different zones of the studied diffraction patterns. This complexity was solved by a dimensional reduction using multivariate statistics, obtaining R 2 >0.90 in calibration studies. Results indicated that imaging device captured the variance produced due to changes in concentrations of protein compounds in despite of changes produced by pH and reagents addition. Therefore, laser-backscattering imaging was capable of monitoring the digestion of egg white gel during gastric and intestinal phases. Highlights: The use of laser-backscattering imaging to model protein digestion was studied. Physicochemical analyses were done in order to evaluate matrix changes. Evolution of protein compounds was different depending on the digestive phase. The imaging device registered the variability generated over digestion process. High correlation between imaging data and protein compounds changes was obtained.